1975
DOI: 10.1021/bi00692a031
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of fractionated calf thymus chromatin by RNA polymerase of calf thymus and Escherichia coli

Abstract: Calf thymus chromatin has been sheared and fractionated on sucrose gradients. Approximately 5-10% of the chromatin is resolved from the bulk of the imput chromatin as a slowly sedimenting fraction. The protein/DNA ratio of the slowly sedimenting fraction is not greatly different from the protein/DNA ratio of the more rapidly sedimenting chromatin fraction. Analysis of DNA of the chromatin fractions by CsC1 equilibrium density gradient centrifugation indicates that DNA of the slowly sedimenting fraction is depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…As these experiments measure the accessibility of DNA sequences within chromatin for transcription and not the accuracy of initiation differences in the frequency of transcription of individual RNA species in vivo and in vitro might result from the use of a heterologous polymerase. Using fractionated calf thymus chromatin, Henner et al (1975) have shown that in most cases the rate of RNA synthesis with E. coli RNA polymerase is greater than the rate with homologous RNA polymerase. The increase in rate of RNA synthesis could reflect a change in the frequency with which "correct" sequences are transcribed or an increase in the number of sequences being transcribed.…”
Section: Discussionmentioning
confidence: 99%
“…As these experiments measure the accessibility of DNA sequences within chromatin for transcription and not the accuracy of initiation differences in the frequency of transcription of individual RNA species in vivo and in vitro might result from the use of a heterologous polymerase. Using fractionated calf thymus chromatin, Henner et al (1975) have shown that in most cases the rate of RNA synthesis with E. coli RNA polymerase is greater than the rate with homologous RNA polymerase. The increase in rate of RNA synthesis could reflect a change in the frequency with which "correct" sequences are transcribed or an increase in the number of sequences being transcribed.…”
Section: Discussionmentioning
confidence: 99%
“…After washing 4 times with 10 mL of 10% trichloroacetic acid in 40 mM sodium pyrophosphate, the filter was incubated wtih 1 mL of Protosol (NEN) for 10 h, and then 10 drops of acetic acid and 15 mL of Triton-toluene (Austin et al, 1973) scintillation fluid were added. RNA polymerase preparations were obtained as described by Henner et al (1975).…”
Section: Methodsmentioning
confidence: 99%
“…Paul, 1969) have made it increasingly desirable to separate transcriptionally active chromatin from total chromatin. Fractionation has been attempted by a variety of techniques including mechanical breakage (Arnold and Young, 1974;Chesterton et al, 1974;Clark and Felsenfeld, 1971) or nuclease digestion (Gottesfeld et al, 1974) followed by fractionation techniques based on differences in size (Janowski et al, 1972), density (Frenster et al, 1963;McCarthy et al, 1974;Henner et al, 1975), and charge (Simpson, 1974).…”
mentioning
confidence: 99%
“…The homogenate was filtered through cheesecloth and centrifuged at 500g for 15 min (4 °C) to pellet the nuclei. The nuclei were then homogenized as above in 100 mL of 0.3 M sucrose containing 10 mM Tris-Cl (pH 8.0), 3 mM CaCl2, 5 mM magnesium acetate, 5 mM dithiothreitol, 0.1% Triton X-100 (Henner et al, 1975), heparin, dextran sulfate (20 gg/mL), and poly(vinyl sulfate) (20 µg/mL•) to remove ribosomes adhering to the endoplasmic reticulum associated with the nucleus. The washed nuclei and postnuclear supernatant were (separately) centrifuged at 18000g for 25 min.…”
mentioning
confidence: 99%